Ophthalmological Considerations for COVID-19 Vaccination in Patients with Inflammatory Eye Diseases and Autoimmune Disorders - Chau, Charlene Y. C. (Ophthalmol Ther, 2021)
The global impact imposed by the coronavirus disease 2019 (COVID-19) pandemic may be soon alleviated by the introduction and worldwide dissemination of safe and effective vaccines. This expedited timetable for development and approval of COVID-19 vaccines is an unprecedented extraordinary, concerted achievement by the scientific community. With the pending global rollout of vaccines, each with different mechanisms of action, physicians of various specialties will need to identify vulnerable patient groups for special considerations or advice. In this commentary, we analyse the important considerations for COVID-19 vaccines in patients with inflammatory eye diseases. Scrutiny of immunogenicity and adverse effects, particularly antibody-dependent enhancement, would better help in counselling these patients undergoing vaccination. More research on pharmacovigilance would allow for tailored guidelines and personalised management strategies.